Perubahan Tema Iklan Menurut Siklus Hidup Produk - Krisna, Marselinus (Jurnal ILMU KOMUNIKASI, 2011)
Abstract: This research is an descriptive qualitative study about the changes of TV commercial’s themes of Sony PlayStation console in USA at 1995-2010. As human beings, the product has its life cycle. The life cycle of products is very influential in the formation of advertising messages. The Sony PlayStation is one brand of video game console generation to the five released by Sony Computer Entertainment and the most popular in the history of the gaming industry. The life cycle of PlayStation consoles reaches its peak at the time of appearance of the PlayStation 2 console. During the life cycle of the last PlayStation has released several television commercials used to promote this console for the consumer. Abstrak: Riset ini merupakan studi deskriptif kualitatif tentang perubahan tema iklan televisi dari produk konsol Sony PlayStation di Amerika Serikat pada periode 1995-2010. Seperti manusia, produk juga memiliki siklus hidup. Siklus hidup produk sangat mempengaruhi pembeuatan pesan iklan. Sony PlayStation adalah salah satu merek generasi konsol video game yang dikeluarkan oleh Sony Computer Entertainment dan sangay populer dalam sejarah industri games. Siklus hidup produk konsol PlayStation mencapai puncaknya pada saat dimunculkannya konsol PlayStation 2. Selama periode siklus hidupnya , PlayStation mengeluarkan beberapa iklan televisi yang digunakan untuk mempromosikan konsol kepada para konsumen.